Militia, in Henry S. Geyer, Digest of the Laws of Missouri Territory, at 281, § 4 (1818). - (:unkn) unknown (General Publisher, 1818)
Each militia man shall provide himself, with-in one month from the date of his enrollment with a good musket, a sufficient bayonet and belt, or a fusil, two spare flints, a knapsack and pouch with a box there-in to contain twentyfour cartridges suited to the bore of his musket or fusil, each cartridge to contain a pro-per quantity of powder and ball: or a good rifle, knap-sack, pouch and powder horn with twenty balls suited to the bore of his rifle, and a quarter of a pound of powe-der
--
Keywords: ARMED FORCES